Utilization of malted barley flour as replacement of wheat flour to improve technological, rheological, physicochemical, and organoleptic parameters of fortified breads - Aslam, Jawed; Hussain, Ashiq; Mueen Ud-Din, Ghulam; Kausar, Tusneem; Siddique, Tahira; Kabir, Khurram; Gorsi, Faiza Iftikhar; Haroon, Haseeb; Nisar, Rizwan; Noreen, Saima; Rocha, João Miguel; Ozogul, Fatih; et al. (Frontiers in Sustainable Food Systems, 2023)
Introduction Flours from cereal grains have the potential to be used in the production of bakery products, especially breads, and the addition of other non–wheat plant materials in the form of flours, extracts and malts has always been the area of interest for food producers. Methods In this research work, barley grains were converted into barley malt flour (BMF), by adopting a series of processes, including steeping, germination, kilning, drying and milling. With the aim of compensating the role of commercial bread improvers, wheat flour was replaced at 0, 2.5, 5, 7.5, and 10% levels with BMF, to study the effect of BMF on physicochemical and sensory characteristics of bread. Results and discussion Chemical analysis of flours revealed that ash, fat, moisture, protein and fibers were found greater in BMF and BMF–incorporated composite flours, as compared to wheat flour. Significant increases in water absorption and decrease in dough stability, dough development time and falling number were noticed, as a result of an increase in the replacement level of BMF. Water absorption of control dough was 58.03%, which increased to 58.77% in composite flour having 10% BMF, whereas dough development time, dough stability and α–amylase activity of control, were 6.97 min, 12 min, and 736 s, respectively, which were decreased to 3.83 min, 4.73 min, and 360 s, respectively in composite flour having 10% BMF. The internal and external characteristics of breads obtained the best sensorial score at 5% replacement level of BMF, and deterioration in the quality of breads was noticed, as the level of BMF was further increased to 7.5 and 10%. Hence, breads developed with 5% BMF and 95% wheat flour, were not only nutritionally rich, but were also with optimum physical and sensory features. BMF could prove a useful alternate ingredient of wheat flour, and a cost-effective replacement of commercially available bread improvers, in the breads manufacturing process in replacement of synthetic bread improvers.